Modelling of multi-scale processes of formation of bottom and shelf waters in the southern part of the Weddell Sea - Maderich, V.; Terletska, K.; Brovchenko, I. (Ukrainian Antarctic Journal, 2017)
The main objective of the study is numerical analysis of the influence of the bottom topography on the flow of waters transformed under the ice shelf of Ronne-Filchner (ice waters), on the shelf and continental slope in the Weddell Sea. The numerical methods were applied in modeling by mean of the SCHISM model with unstructured mesh. The simulation results showed that under the action of buoyancy forces, Coriolis and friction in the baroclinic ocean, the flow of water from the Ronne- Filchner glacier on the edge of the shelf and the continental slope is divided into three: one branch flows into the abyssal of the Weddell Sea, the other flows along the continental shelf, while the third, the largest part of the flow, turns to the shelf and fills the Ronne depression, returning under the Ronne-Filchner glacier. We conclude that recirculation of the ice waters can significantly affect the evaluation of bottom water production in the Weddell Sea.